The Legal Argumentation Regulatory Framework for Management of Sharia Funding and Risk Loans in Indonesia - Jefry Tarantang; Ni Nyoman Adi Astiti (IAIN Manado, 2023)
This study discusses legal arguments related to Indonesia's regulatory framework for managing Sharia funding and loan risk. This study uses a legal analysis approach concerning the principles of the state constitution, Islamic banking laws, the fatwa of the Indonesian Ulema Council (MUI), and regulations from the Financial Services Authority (OJK). This arrangement aims to protect consumer interests, ensure compliance with Sharia principles, and maintain the sustainability of the Sharia financial industry in Indonesia. This study uses qualitative research with data search methods, namely through library research sources and literature studies through library research in scientific journals, books, papers, and articles directly related to the research problem under study. It has the purpose of doing a description of the problem under study. In conclusion, this regulatory framework is essential to protect consumer interests, ensure compliance with Sharia principles, and maintain sustainability in Indonesia's Islamic finance industry. These regulations are based on solid legal principles, such as the country's constitution, laws, MUI fatwas, and OJK regulations. This research contributes to understanding the legal arguments regarding Indonesia's regulatory framework for managing Sharia funding and loan risk. It can be a reference for further research and development in this field..